Tumor of the carotid body (paraganglioma). - Franklin, J (1990)
Carotid body tumours (paragangliomas) are uncommon but rather an interesting pathology, due to the controversy that still remains regarding their histopathologic behaviour (malignancy?), as well as their diagnosis and management. Because of its nature being composed of chemoreceptor paraganglionic tissue, the carotid body responds to lower partial pressure of oxygen and can cause severe cardiovascular disturbances. Based upon a series of 12 cases, the authors reviewed this pathology in detail, and discussed the methods of diagnosis and treatment, which they considered more appropriate.